SHEAR BEHAVIOR OF REINFORCED CONCRETE BEAMS STRENGTHENED BY CFRP STRIPS: - Mohammed Abd, Lubna (Journal of Applied Engineering Science, 2021)
In this research, (12) normal reinforced concrete beams are used with dimensions (110*10*20) cm, the compressive strength for all specimens is 30 MPa. Longitudinal steel is deformed bars 2Ø12mm with Ø6 mm transverse reinforcement which is deformed bars also for different spacing 5 cm, 10 cm and 15 cm. After casting the specimens and removing them from the molds, they left for about 28 days. They tied by CFRP strips with different shapes of tying (tied, inclined and X- shaped). They are all testing with two points load by a hydraulic machine for determining (Pu, P cr, maximum deflection and modes of failure) and compared among their results with the specimens without CFRP strips. From the experimental program, the excellent behavior of the specimens with the X-shaped strips especially with the Pu which is 70% increment and maximum deflection is 39% decrement. The addition of CFRP strips as a tying material helps to increase the strength of concrete and bearing against loads also, changes and decreases the flexural and shear failure and combined failure.